Análise da rede política do turismo brasileiro. - Brandão, Pamela de Medeiros (2010)
The dissertation examines the influence of relationships among actors from Brazilian Tourism Political Network who compose the National Council of Tourism in the drafting of the National Tourism Plans (PNT) - PNTs 2003/2007 and 2007/2010, focusing on two main types of interaction: cooperation and information exchange. Therefore, the study departed from the understanding that the concept of tourism as a human phenomenon is configured as an essential conceptual basis for the development, implementation and analysis of public policies. The application of Network Theory and Social Network Analysis serves as an analytical tool, in addition, the use of concepts of Policy Networks enabled to interpret, in distinct aspects, the social reality of tourism in a more precise and detailed way. The study had a cross-sectional with a longitudinal perspective and case study was adopted, thus enabling to apply the model of social network analysis and qualitative approach. Through the survey conducted, it was found that the drafting process of National Tourism Plans was the result of the interaction of a complex network of actors from public and private initiatives, who compose the National Council of Tourism, and that their power of influence came out simultaneously, but not symmetrically, for both their performance/intervention in the meetings, and the possession of economic and organizational resources. Hence, the establishment of partnerships and information exchanges among the actors were underlying to the PNT drafting process, both in problems perception and insertion in the government agenda, as in making proposals to solve them, thus guiding the construction of large programs and programs contained in both investigated plans.